Comprehensive Phytochemical Profiling and Quantitative Analysis of Bioactive Compounds in Centella asiatica Leaves with In Vivo Assessment of Anti-inflammatory, Antioxidant, and Anticancer Efficacy Using Rodent Models - Ramasamy, N.; Mali, Neha; Yadav, Paresh Kapoor; Kumar, Anil; Vyas, Navdha; Rathore, Urmila; Kathiresan, Ponnudurai; Pandey, Ekta; Das, Nihar Ranjan (Journal of Neonatal Surgery, 2025)
Background: Centella asiatica (L.) Urban, commonly known as Gotu Kola, has long been utilized in traditional medicine systems for its reputed wound healing, neuroprotective, and anti-inflammatory effects. Despite widespread traditional use, comprehensive studies integrating detailed phytochemical profiling and in vivo evaluation of multiple pharmacological activities remain limited. Objectives: This study aimed to (i) perform thorough phytochemical profiling and quantitative analysis of bioactive compounds in C. asiatica leaves, and (ii) evaluate their anti-inflammatory, antioxidant, and anticancer efficacy using rodent models. Methods: Leaves of C. asiatica were collected, authenticated, and extracted using various solvents (hexane, ethyl acetate, ethanol, aqueous). Phytochemical screening, high-performance liquid chromatography (HPLC), gas chromatography-mass spectrometry (GC-MS), and Fourier-transform infrared spectroscopy (FTIR) were used for profiling and quantification of key compounds such as asiaticoside, madecassoside, and asiatic acid. Anti-inflammatory activity was assessed using a carrageenan-induced paw edema model. Antioxidant potential was evaluated by measuring hepatic SOD, CAT, GPx activities, and MDA levels after CCl₄-induced oxidative stress. Anticancer efficacy was investigated in a DMBA-induced skin papilloma model. Results: Ethanol extract showed the highest yield, total phenolic content (TPC), and total flavonoid content (TFC). HPLC analysis confirmed significant amounts of asiaticoside (32.7 ± 1.2 mg/g), madecassoside (27.8 ± 1.0 mg/g), and asiatic acid (22.1 ± 0.7 mg/g). In vivo studies demonstrated significant inhibition of paw edema (61.2 ± 2.1% at 400 mg/kg), enhanced antioxidant enzyme activities (SOD, CAT, GPx), reduced MDA levels, and marked reduction in tumor incidence and volume in the DMBA model. Conclusion: The findings support the multi-target therapeutic potential of C. asiatica leaf extracts, attributed to their rich triterpenoid and phenolic composition. These results justify further mechanistic studies and clinical evaluation to develop standardized C. asiatica-based formulations for integrative treatment of inflammation, oxidative stress-related disorders, and cancer.